Best practices in leadership development and organization change how the best companies ensure meaningful change and sustainable leadership - Carter, Louis (San Francisco Pfeiffer, 2005)
In this important book, successful organizations?including well-known companies such as Agilent Technologies, Corning, GE Capital, Hewlett Packard, Honeywell Aerospace, Lockheed Martin, MIT, Motorola, and Praxair?share their most effective approaches, tools, and specific methods for leadership development and organizational change. These exemplary organizations serve as models for leadership development and organizational change because they
Includes bibliographical references and index.
Keywords: Leadership -United States -Case studies